KARAKTERISTIK ELEMEN PERANCANGAN KOTA DI JALUR KORIDOR JALAN VETERAN DENPASAR - I Kadek Ady Widyatmika; Frysa Wiriantari; Bagus Made Arjana (Jurnal Anala, 2017)
Satria area along the corridor of Veteran Street will be used as research object to find the characteristic, the potential, and the existing problem on each elements of Urban Design. The elements of discussion which are land management, building management, circulation and open parking space, pedestrian ways, support activity, signage system, preservation and conservation. The methodology that will be used area data collection, data arragment, data analysis, then will be ended with conclusion and research purpose.Key Word : charateristic, element of urban design, corridor.